If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 2ln(3x + -8) = 22 Reorder the terms: 8 + 2ln(-8 + 3x) = 22 8 + (-8 * 2ln + 3x * 2ln) = 22 8 + (-16ln + 6lnx) = 22 Solving 8 + -16ln + 6lnx = 22 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -16ln + -8 + 6lnx = 22 + -8 Reorder the terms: 8 + -8 + -16ln + 6lnx = 22 + -8 Combine like terms: 8 + -8 = 0 0 + -16ln + 6lnx = 22 + -8 -16ln + 6lnx = 22 + -8 Combine like terms: 22 + -8 = 14 -16ln + 6lnx = 14 Reorder the terms: -14 + -16ln + 6lnx = 14 + -14 Combine like terms: 14 + -14 = 0 -14 + -16ln + 6lnx = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-7 + -8ln + 3lnx) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-7 + -8ln + 3lnx)' equal to zero and attempt to solve: Simplifying -7 + -8ln + 3lnx = 0 Solving -7 + -8ln + 3lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '7' to each side of the equation. -7 + -8ln + 7 + 3lnx = 0 + 7 Reorder the terms: -7 + 7 + -8ln + 3lnx = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -8ln + 3lnx = 0 + 7 -8ln + 3lnx = 0 + 7 Combine like terms: 0 + 7 = 7 -8ln + 3lnx = 7 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| y-(-3)=6 | | 3x-3+2x-4=6 | | -6=4x-1 | | 3(-32+25)+7= | | 5x-6+90=3x | | 7(g+4)=49 | | 5xsquare+4=136 | | -14+11=m-2 | | -4x-5(-x+4)=-31 | | 2+7(18+10)= | | 3x+5x-6+90= | | 6m+5=m | | 5x^2-7x+39=0 | | 42-6=6(z+2)+8 | | 5(k+10)=55 | | 37-g=4g | | -8=6-n | | z-z+1+10z= | | 5x+178=3x+152 | | 1.5c_2.4=6 | | 54=6x+3(-7x-12) | | 0.19+0.03(y+2000)=1160 | | 2=35 | | 6n+13-2n=-15 | | 5(x+7)-3x=11 | | -6(-8x+16)=144 | | y-.8=1.4(x-1) | | q-16=2 | | -5x-2(-2x+14)=-34 | | z-z+1+10= | | 2(5n-3)-(n-2)= | | 60r+60=600 |